Neutrophil maturation rate determines the effects of dipeptidyl peptidase 1 inhibition on neutrophil serine protease activity. (7th July 2016) - Gardiner, P; Wikell, C; Clifton, S; Shearer, J; Benjamin, A; Peters, S A
Abstract : Background and Purpose: Neutrophil serine proteases (NSPs) are activated by dipeptidyl peptidase 1 (DPP1) during neutrophil maturation. The effects of neutrophil turnover rate on NSP activity following DPP1 inhibition was studied in a rat pharmacokinetic/pharmacodynamic model. Experimental Approach: Rats were treated with a DPP1 inhibitor twice daily for up to 14 days; NSP activity was measured in onset or recovery studies, and an indirect response model was fitted to the data to estimate the turnover rate of the response. Key Results: Maximum NSP inhibition was achieved after 8 days of treatment and a reduction of around 75% NSP activity was achieved at 75% in vitro DPP1 inhibition. Both the rate of inhibition and recovery of NSP activity were consistent with a neutrophil turnover rate of between 4–6 days. Using human neutrophil turnover rate, it is predicted that maximum NSP inhibition following DPP1 inhibition takes around 20 days in human. Conclusions and Implications: Following inhibition of DPP1 in the rat, the NSP activity was determined by the amount of DPP1 inhibition and the turnover of neutrophils and is thus supportive of the role of neutrophil maturation in the activation of NSPs. Clinical trials to monitor the effect of a DPP1 inhibitor on NSPs should take into account the delay in maximal response on the one hand as well as the potential delay in a return to baseline NSP levels following cessation of treatment.